STRATEGI PENERAPAN KNOWLEDGE MANAGEMENT SYSTEM PADA APLIKASI IT HELPDESK: STUDI KASUS PT ASURANSI TRI PAKARTA - Machfudin, Turifah (POLITEKNIK LP3I JAKARTA, 2014)
The use of information technology at this time is needed to support the company's business. PT. Tripakarta insurance is one of the companies that had implemented knowledge management systems on the IT helpdesk application online. This application’s function is to handle information need around insurance business or user’s complaint in related to questions, service, techincal support or complain about any product and service by system to make easier the searching of solving problem by team. By implementing knowledge management system in IT application Helpdesk, it should be measured priority scale measurement to understand the work of that application. In this research, the used method is descriptive analysis and Analytical Hierarchy Process (AHP). Meanwhile, the collection data method is done by observation, library study and interview to the chosen sample by using purposive sampling method. This research wished can help company in choosing the best strategy in making decision for developing IT helpdesk application and to increase human resource quality regarding to the related job with job performance. Keywords: Information Technology, Knowledge Management System, IT Helpdesk Application, Priority Scale Measurement, Analytical Hierarchy Process (AHP).